EXPORT DIVERSIFICATION, CONCENTRATIONANDECONOMIC GROWTHINTHE POLANDINTHE PERIOD1995-2009 (Research Bulletins of the Faculty of Economic Sciences, 2021)
The main aim of the paper is to analyze the relationship between export diversification, concentration and economic growth in Poland in the period 1995-2009.  This article consists of two parts. The first part concerns the theoretical analysis of the relationships between the degree of exports diversification (concentration) and economic growth. The next part examines the relationship between the degree of exports concentration and economic growth in Poland using a vector autoregression model (VAR). There have been estimated elasticity coefficients of GDP per capita to changes in the exports concentration on the basis of impulse response functions. This was followed by decomposition of GDP per capita in order to estimate the impact of changes in GDP per capita and the degree of exports concentration on the variability of GDP per capita in Poland. Results of this study revealed the existence of nonlinear relationship between the degree of exports concentration and GDP per capita in Poland in the period 1995-2009.
Keywords: exports diversification, exports concentration, economic growth